GoFood Vs ShopeeFood: Manakah yang Menjadi Pilihan Generasi Z? - Faizah, Fita Nurotul; Zulfaturrohmaniyah, Zulfaturrohmaniyah (Al-Tijary, 2022)
The presence of online food delivery platform makes it easier for people to order food online without having to come directly to the restaurant. This study aims to ascertain Generation Z's preference for online food delivery between ShopeeFood and GoFood based on the notion of the marketing mix from an Islamic economics perspective. A comparative descriptive methodology was adopted. The research participants at the time were Generation Z from Semarang City. About the sample that was obtained through accidental sampling under non-probability sampling. While research data was gathered from observations, questionnaires, observations, interviews, and documentation. According to the findings, Generation Z prefers ShopeeFood over GoFood. From a sharia economic perspective, this can be seen in the 7P marketing mix, which includes: pragmatism & product aspects, which explain that even though there are more GoFood merchants, Generation Z prefers ShopeeFood because the necessary menu options are also available in the market, while the pertinence & promotion aspect, which explains ShopeeFood offers more promos even though it claims the promo is easier on GoFood, and the palliation & price aspect, where Shop. The results are not significantly different for the factors of persistence and process, patience and environment, peer support and people, pedagogy and environment, and so on. The implications of this study for both platforms need to expand the reach of merchants so that the availability of popular menus at competitive prices can strengthen promotional strategies and can be an important factor to maintain consumer satisfaction.